Respuesta :
Answer:
She did not multiply equation 3 in step 2 by the correct value.
Step-by-step explanation:
Given:
[tex]3x+2y+3z=5\\7x+y+7z=-1\\4x-4y-z=-3[/tex]
In order to solve this, we need to eliminate any one variable and then form a simultaneous equation with the remaining two variables. Then, we nee to solve the simultaneous equation.
Here, Galena is trying to eliminate the variable [tex]z[/tex] first.
Step 1: She multiplies equation (3) by 3 and adds it to equation (1)
Let us multiply equation (3) by 3
[tex](4x-4y-z=-3)\times 3 = (3\times 4x)-(3\times 4y)-(3\times z)=3\times -3\\(4x-4y-z=-3)\times 3 =12x-12y-3z=-9[/tex]
Now, adding this to equation 1 will cancel out z terms.
[tex]12x-12y-3z+3x+2y+3z=-9+5\\(12x+3x)+(-12y+2y)+(3z-3z)=-4\\15x-10y+0=-4[/tex]
Now, she need to make one more equation in [tex]x\ and \ y[/tex].
Step 2: She multiplies equation (3) by -7 and adds it to equation (2)
Multiplying equation (3) by -7 will give,
[tex](4x-4y-z=-3)\times -7 = (-7\times 4x)-(-7\times 4y)-(-7\times z)=-7\times -3\\(4x-4y-z=-3)\times 3 =-28x+28y+7z=21[/tex]
Now, adding this to equation 2 will not cancel out z terms.
[tex]-28x+28y+7z+7x+y+7z=21-1\\(-28x+7x)+(28y+y)+(7z+7z)=20\\-21x+29y+14z=20[/tex]
So, she makes mistake in step 2 as the [tex]z[/tex] terms are not being cancelled.
Answer:
She did not multiply equation 3 in step 2 by the correct value.
Step-by-step explanation: